Parental Health Behaviors and Demographic Factors as Determinants of Immunization Completeness - Davina, Aifa Putri; Zahrani, Ayu; Arrantissi, Syauqi Hanif; Sintowati, Retno; Romadhon, Yusuf Alam (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: This study aims to analyze the demographic determinants and parental health behaviors associated with the completeness of immunization in children under five. Methodology: This study used a cross-sectional design, where data were collected at one point in time to analyze the relationship between independent variables and the completeness of booster immunization in children aged 24-60 months. Results: This study found that child gender had a significant effect on immunization completeness, with girls being more likely to receive complete booster immunization than boys. Meanwhile, birth order, maternal age at delivery, and delivery method did not show a significant association with immunization completeness, in contrast to the results of previous studies which mentioned that children with higher birth order tend to have lower immunization coverage. Applications/Originality/Value: This study has practical applications as input for policy makers and immunization program implementers to design more evidence-based and contextualized strategies, taking into account parental health behaviors as well as family demographic characteristics. The novelty of this study lies in its focus on the completeness of booster immunization in children aged 24-60 months, a group that has rarely been studied in Indonesia, as most previous studies have focused on basic immunization and children under 24 months. The importance of this study is also reflected in its emphasis on parental behavioral variables, such as exclusive breastfeeding and paternal smoking habits, which are less explored but have great potential to influence child immunization coverage.